AZAS “PRESUMPTION OF INNOCENCE” ATAU AZAS” PRADUGA TAK BERSALAH” DI NEGARA HUKUM INDONESIA SEBUAH PEMAHAMAN EMPIRIK - Kosmas Minggu (Bajang Institute, 2024)
The purpose of this study is to discuss the phenomena that occur in Indonesian human rights originating from the nation's philosophy and view of life, namely Pancasila. This is in the Preamble and Body of the 1945 Constitution in Article 1 paragraph (3) as a state law. Which includes all human rights in the fields of law, politics, economics and socio-culture. While the existence of the Principle, Presumption, Of Innocence or the principle of the presumption of innocence is one aspect that is included in this goal. Therefore, the scope of the problem presented is simple, namely how the existence of the presumption of lawlessness has been implemented, both by law enforcement, the mass media, as well as by